Reef development during the Oligo-Miocene transition: A new Aquitanian record from Guajira Colombia (2016)
Caribbean Coral reefs experienced important changes at the Oligo-Miocene transition. The record shows a decrease in modern type reefs at the end of the Oligocene, while non-extensive reefs, mostly confined to shallow or siliciclastic dominated environments, were formed during the early Miocene. At the same time, there are several changes in Caribbean Sea environment including tectonic events, ocean circulation, variations in sea level and temperature. To explore the relationship between regional to global environmental factors on coral evolution and carbonate depositional patterns, we evaluated an Early Miocene (Aquitanian) paleo-reef located at the Siamaná Formation in the Guajira Peninsula, Northern Colombia. Furthermore, we compared the reef with updated ages and coral composition at other Caribbean reefs deposited during the same interval. Siamaná reefs are mainly composed of framestones and rudstones constituted by typical corals of the Oligocene – Miocene taxa (e.g. Agathiphyllia sp., Antiguastrea sp., Diploastrea spp., Siderastrea siderea), most of them in life position forming well consolidated fringing reefs systems with almost 400 m of extension. Comparison with analogous assemblages indicates deposition in similar conditions reported from late Oligocene reefs, but no decrease in coral diversity and/or reduction of the building capacity during the early Miocene were found. Thin sections and total carbon contents analysis also shows absence of siliciclastic input but highest values of carbonate (70.2% to 98%). Results indicate that Siamaná paleo-reef responded to global environmental changes but, their development is also largely controlled by regional patterns where their shallow marine biotas evolved independently. Siamaná collapse is related to a rapid increase in relative sea level and to an increase in regional tectonic subsidence at a later stage (Aquitanian and Burdigarian), rather than an increase in sediment supply during the Oligocene-Miocene transition.